Improved resource-saving technology of soil cultivation and use of bio-preparations for spring cereals crops under conditions of central zone of North-East of European part of Russia - L. M. Kozlova; F. A. Popov; E. N. Noskova; V. L. Ivanov (Аграрная наука Евро-Северо-Востока, 2017)
Results of 2013-2015 three-factor experiments on study of ways of basic, pre-sowing soil cultivation and use of bio-preparations were presented in the article; their influence on productivity of plant species of crops rotation chain was showed. Correlation relations between productivity of spring cereals and grain-forage crops and storage of productive moisture and soil density of arable layer of sod-podzolic middle-clay soil, degree of dockage of sowings with perennial and minority weeds. Analysis of energetic and economic efficiency of cultivation was shown that technology on the basis of ploughing with KBM-4.2 soil cultivation and inputting of bio-preparation Pseudobacterin-2 was most profitable for spring wheat (coefficient of energetic efficiency was 2.27; self-cost - 3453 rubles per ton, profitablility 75%). Technology on the basis of ploughing with KPS soil cultivation and inputting of bio-preparation Pseudobacterin-2 was effective for barley cultivation (coefficient of energetic efficiency was 3.26; self-cost - 2326 rubles per ton, profitablility 115%). Technology which includes surface combining cultivation with pre-sowing treatment with APPN-2.1 combined aggregate and inputting of bio-preparation on the basis of strain S. hygroscopiсus А4 was highly effective for cultivation of paes-oat mixture (coefficient of energetic efficiency was 4.60; self-cost - 1378 rubles per ton, profitablility 64%).